Formulation, Characterization And In-Vitro Evaluation Of Acrylic Polymer Loaded Aceclofenac Microspheres - A.SHANMUGARATHINAM; D.VIDHYESWARI; A.PURATCHIKODY (International Journal of Pharma and Bio Sciences, 2011)
Microspheres can be utilized for precise delivery of drugs and reduce the drug concentrations at sites other than the target organ. The present study is aimed to prepare and evaluate the aceclofenac microspheres using an acrylic polymer Eudragit–S 100. Aceclofenac microspheres were prepared by o/w solvent evaporation method and evaluated for its percentage yield, particle size, entrapment efficiency and its in-vitro release. Percentage yield and entrapment efficiency of formulated microspheres were found to be high. The mean diameter of microspheres were found to be within 91 – 109µm. In-vitro release study on phosphate buffer pH 6.8 showed 58 – 67%.